Program unggulan kampung iklim (proklim) berbasis pemberdayaan masyarakat - Dodi Faedlulloh; Bambang Irawan; Retnayu Prasetyanti (Universitas Merdeka Malang, 2019)
TThis paper is intended to present a comparative analysis of the implementation of a community empowerment based Kampung Climate's Leading Program (ProKlim) in Jati Village, East Jakarta and Kebon Kosong Village, Central Jakarta. The result of this research indicates that both in Kebon Kosong Village and Kelurahan Jati have emphasized aspects of community empowerment in the implementation of ProKlim mainly in climate change adaptation and mitigation activities. Empowerment and participation of communities in Jati Village is considered improperly managed, while in Kebon Kosong Village, the implementation of ProKlim is more coherent and sustainable. However in substance, ProKlim has been well implemented in each locus. Further in practice, ProKlim, with a persistent management, is perceived to be able to manage a microclimate which gives a wider impact on temperature deterioration in the capital city. DOI: https://doi.org/10.26905/pjiap.v4i1.2364